The Iconographic Analysis of Speculum Humanae Salvationis Miniatures from the Collection of N. Ugodina - Rogov, Mikhail A. (Actual Problems of Theory and History of Art, 2016)
The unknown fragments of a German illuminated manuscript were discovered in January 2015. They were introduced for a scholarly usage and studied in this paper as an object of medieval art history including codicological, stilystical and iconographic analyses. This article is devoted to their attribution as sister miniatures of the Bavarian translation of Speculum humanae salvationis (Spiegel menschlicher Behältnis), which were previously considered lost from the Königsberg Public Library during the Second World War in 1944, to their program, iconographic motifs, and stylistic similarities with the miniatures made in Upper Germany workshops of the 15th century, as well as to the subsequent existence of this artwork.
Keywords: speculum humanae salvationis; Upper Germany workshops; codicology; iconography; sister miniatures